Transcatheter Aortic Valve Replacement Program in the Post–Food and Drug Administration Approval Era. Issue 1 (January 2015) - Melby, Spencer J.; Bess, Kyle M.; Isbell, Kayla D.; Sasse, Mark F.; Leesar, Massoud A.; Alli, Oluseun O.; Singh, Satinder P.; Jernigan, Lindsay B.; George, James F.; Davies, James E.
<x xml:space="preserve">Abstract</x> Objective Transcatheter aortic valve replacement (TAVR) has recently become a suitable alternative for treatment of symptomatic aortic stenosis in patients who are at very high risk for morbidity and mortality with conventional corrective surgery. In the fall of 2011, the Food and Drug Administration approved the use of TAVR, allowing for reimbursement at institutions outside of investigative trials. We report the initiation of a TAVR-based program at an academic tertiary care facility that did not participate in the Placement of Aortic Transcatheter Valves (PARTNER) 1 or PARTNER II trials. Methods A total of 160 patients were evaluated for TAVR from May 2012 through June 2013. Transcatheter aortic valve replacement was found to be appropriate for 50 (31%). Results In this experience, morbidity and mortality were similar to those reported for the PARTNER trial (30-day hospital mortality was 8%). A single case of presumed cerebrovascular accident was observed. These results demonstrate that the real-world application can be done with comparable results. Implementation of lessons learned in the trials allowed a very short learning curve and excellent results after only a limited number of patients. Use of computed tomography reconstructed images for operative planning, including fluoroscopic angle, facilitated minimal use of contrast in each case. Conclusions Transcatheter aortic valve replacement is a viable option for patients at very high risk for surgical intervention in the post–Food and Drug Administration approval era. Real-world results comparable with published outcomes from experienced centers involved in the PARTNER trial can be achieved.